Prophetic Ethics in the Digital Economy: Integrating Qanāʿah and Key Hadith Foundations for Regulating Consumptive Desire - Haidi Hajar Widagdo (Journal of Innovative and Creativity, 2026)
Digital consumer environments increasingly operate as low-friction choice architectures in which e-commerce, social commerce, live-streaming commerce, and buy-now-pay-later (BNPL) mechanisms compress deliberation time and amplify persuasive cues through algorithmic curation, social proof, and time-limited promotions. Under these conditions, consumer judgment is frequently displaced from reflective evaluation toward affect-laden, desire-driven purchasing, normalizing impulsive micro-transactions and debt-enabled consumption. While digital consumption literacy is often framed as a technical or informational competence, this framing remains inadequate for addressing the ethical and motivational dynamics that sustain non-satiative desire and recurrent overconsumption. Consequently, there is a need for an evaluative framework that can regulate preference formation and provide a stable welfare anchor in digitally mediated markets, particularly one that can translate normative commitments into operational competencies for decision-making. The study purpose was to formulate a coherent hadith-based framework for digital consumption literacy by operationalizing qanāʿah (contented sufficiency) as a mode of preference governance in the digital economy, where e-commerce, social commerce, live-streaming commerce, and buy-now-pay-later (BNPL) services reduce transactional friction and intensify persuasive stimuli. The study also aimed to clarify how Prophetic ethics can function as an evaluative anchor for consumer decision-making amid algorithmic curation, social proof, and promotional time pressure that frequently precipitate impulsive buying and desire-driven consumption. Materials and methods. This research employed a qualitative text-based design with a focused thematic reading of selected Prophetic reports as the primary corpus. Analytical procedures included (i) segmenting each hadith into propositional meaning units, (ii) identifying normative diction and the internal logic of claims (premiseimplication), (iii) deriving core themes related to insatiability and sufficiency, and (iv) constructing a conceptual model that translates these themes into measurable competencies of digital consumption literacy. Contemporary scholarly literature on digital persuasion and consumer behavior was used as contextual support rather than as a determinant of textual meaning. Results. The analysis indicates that the “valley of gold” narration provides a normative diagnosis of non-satiative desire that is readily amplified by status competition and platform affordances, while the “daily provision” narration compresses welfare into observable sufficiency benchmarks (security, bodily well-being, and daily provision). Synthesizing both, qanāʿah emerges as a value-informed stopping rule that recalibrates evaluation from maximization toward kifāyah-oriented adequacy, constraining isrāf and tabdhīr and internalizing social externalities. Conclusions. The proposed framework positions Prophetic ethics as an actionable architecture for digital consumption literacy by specifying competencies such as needwant differentiation, scrutiny of persuasive tactics, BNPL risk appraisal, and attention governance. This model advances a conceptually rigorous pathway for ethically resilient consumer behavior in digitally mediated markets.